Implementasi Pembelajaran PKn Berbasis Proyek untuk Menumbuhkan Sikap Disiplin dan Tanggung Jawab Siswa SDIT AL Azhar Pekanbaru - Hasibuan, Nurkhadizah; Yanti, Indres Novri; Rahayu, Fuji (Journal of Practice Learning and Educational Development, 2026)
Civics Education (PKn) plays a strategic role in shaping students' character, particularly in terms of discipline and responsibility, which are currently key requirements for students' social development in the digital age. However, PKn teaching in elementary schools tends to be informative in nature, meaning that students lack direct experience in applying these values. This study aims to describe the implementation of project-based PKn learning as an effort to foster discipline and responsibility among students at SDIT AL Azhar Pekanbaru. The research approach uses a qualitative method with a case study design. Data were collected through learning observations, interviews with teachers and students, and documentation of project activities carried out in the PKn learning process. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. The results showed that project-based civic education learning was able to improve student discipline through time management, commitment to work schedules, and completion of tasks according to deadlines, while responsibility grew through the division of group tasks, completion of individual parts, and active involvement until the final product of the project. In addition, project-based learning fosters motivation, cooperation, and active participation. Thus, this model is effective when applied in civic education learning to strengthen character building among students in elementary school.